2015
DOI: 10.14198/jhse.2015.10.proc1.35
|View full text |Cite
|
Sign up to set email alerts
|

Competitive sport and self-concept in adolescent

Abstract: D'Anna, C., Rio, L., & Paloma, F. (2015). Competitive sport and self-concept in adolescent. J. Hum. Sport Exerc., 9(Proc1), pp.S425-S429. Self-esteem is the degree to which an individual values himself or herself globally. Several studies have shown that the self-esteem level is a key indicator of positive mental health and well-being. The belief that physical activity and sport are often associated with the best development of self-esteem in adolescent is a commonly held view. However in literature there are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…This study highlights an interesting finding: competitive adolescent rhythmic gymnasts scored higher than recreational in Global Self-Worth or self-esteem. This finding is in line with recent findings also suggesting that both, female and male adolescents who were involved in competitive sports (irrespective of whether they participated in individual or team sports) demonstrated high levels of selfesteem (D'Anna, Rio, & Gomez-Paloma, 2015). Contrary, a previous study found that the self-esteem of young gymnasts (aged 6-13 years) practicing competitive gymnastics was significantly lower than that of girls practicing recreational gymnastics (Amac et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…This study highlights an interesting finding: competitive adolescent rhythmic gymnasts scored higher than recreational in Global Self-Worth or self-esteem. This finding is in line with recent findings also suggesting that both, female and male adolescents who were involved in competitive sports (irrespective of whether they participated in individual or team sports) demonstrated high levels of selfesteem (D'Anna, Rio, & Gomez-Paloma, 2015). Contrary, a previous study found that the self-esteem of young gymnasts (aged 6-13 years) practicing competitive gymnastics was significantly lower than that of girls practicing recreational gymnastics (Amac et al, 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Los resultados más destacables obtenidos en el presente estudio hacen referencia a que los mayores que consideran tener una mejor autoestima personal, son aquellos que realizan actividades físicas frecuentemente. Estos resultados coinciden con otros estudios en los que se han encontrado una correlación positiva entre la práctica de actividad física y la mejora de la autoestima (D´Anna et al, 2015;De-Juanas et al, 2013;Gallego et al, 2012;García et al, 2012;Lobo et al, 2015;Park et al, 2014;Reynaga-Estrada et al, 2016).…”
Section: Discussionunclassified
“…Se ha comprobado que los estudios que relacionan el autoconcepto y la autoestima con distintas variables psicosociales han sido muy numerosos, sin embargo, uno de los aspectos más destacados es el relacionado con los aspectos físicos (Guillén & Ramírez, 2011). Estas relaciones han sido bidireccionales: desde aquellas que establecen relaciones entre la influencia del autoconcepto físico sobre la realización de actividades físicas y deportivas (Guérin, Marsh & Famose, 2004;Marsh, Richards, Johnson, Roche & Tremayne, 1994), a las que analizan la influencia de la actividad física y deportiva sobre el autoconcepto y la autoestima (Álvarez, Cuevas, Lara & González-Hernández, 2015;Bohórquez et al, 2014;D´Anna, Rio & Gomez-Paloma, 2015;De-Juanas et al, 2013;Gallego et al, 2012;García, Marín & Bohórquez, 2012;Kyle, Hernández-Mendo, Reigal & Morales-Sánchez, 2016;Lobo, Batista & Cubo, 2015;Murgui, García & García, 2016;Park et al, 2014;Reguera & Gutiérrez-Sánchez, 2015;Reynaga-Estrada, Arévalo, Verdesoto, Jiménez, Preciado & Morales, 2016).…”
Section: Actividad Física Y Autoestimaunclassified
“…[8] Various studies point to the importance of self-esteem in the settings of sports activities based on the integrative notion of self-esteem mentioned in sports-related literature. D'Anna et al [9] conducted a research to assess self-esteem in a variety of athletes, impact of gender in determining self-esteem. [10] Sport participation has been linked to an increase in self-esteem, according to the previous researches, Wagnsson et al [11] Pedersen and Seidman; [12] Slutzky and Simpkins; [13] and Daniels and Leaper [14] all employed a longitudinal design to look into the relationship between sport activity and self-esteem.…”
Section: Introductionmentioning
confidence: 99%